Loro Blonyo In Current Javanese Culture From Sacredness to Commercialism = Loro Blonyo dalam Budaya jawa Masa Kini Dari Sakral ke Komersial - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT Loro Blonyo is pair of statues which have a close.relationship with traditional farmers in Java. The statues are as a representation of Dewi Sri and Dewa Sadana regarded as symbols of fertility, success, happiness, prosperity, long life, health, and ability to have many children. In Javanese traditional society, Loro Blonyo is placed in the middle of senthong which is called pasren. In Javanese modern society, Loro Blonyo is not placed m pasren, but it is placed in public area. There are two items need to be focused in the research. First, it is focused on Loro Blonyo which is placed in pasren of the Yogyakarta Palace's special room. Second, Loro Blonyo which is placed outside pasren is freely being sale for public as a commercial product. To find out visual language and the hidden message that will be conveyed from Loro Blonyo which located in pasren or outside pasren, the research approaches used are aesthetics which is supported by semiotics and other relevant studies. Loro Blonyo which is located in pasren is originally assumsed from Javanese culture as a representation of Animism's belief, i.e. a belief of ancestor spirit and the God and Goddess of Hindu and Budha. The traditional farmers in Java, still have great respect to Dewi Sri up to now. They hold an offering ceremony before the harvesting time which is called wizvit ceremony. During the ceremony, the farmers make two bundles of rice plant as a representation of married couple which is called mantenan. Loro Blonyo which is located outside pasren is not intended for ritual medium, but for product sale. The are some imitations of Loro Blonyo which located in the pasren. Some of them are modified so that they look more flirtatious, dissection and funnier. There is no unity between movement and mimic. The Craftmen that we have to day are only workers, not the owner of the home industry. Loro Blonyo which is located outside the pasren has lost its spiritual "spirit" and the symbol of fertility, success and prosperity are stated to die.